Macroeconomic Considerations and Motives of Sovereign Wealth Funds Activity - Dariusz Urban (Contemporary Economics)
Sovereign wealth funds are entities regarded as an institutional innovation in the international financial market. Due to the nature of the ownership rights, the investment activity of such entities is still highly controversial. Objections against sovereign wealth funds included the alleged extraeconomic goals of their activity. This article attempts to show that the establishment development and operation of sovereign wealth funds are determined by economic factors. The study presents a description of the international monetary system and the motives for building foreign exchange reserves by countries. It has been evidenced on the basis of the most recent data that some countries have reserves considerably exceeding the level regarded as optimal for the economy. The article presents benefits for the economy from the use of sovereign wealth funds to manage excessive foreign exchange reserves.